2024
DOI: 10.3390/horticulturae10040316
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Preservation of Bioactives in Wild Garlic (Allium ursinum L.) through Advanced Primary Processing

Alena Stupar,
Žarko Kevrešan,
Aleksandra Bajić
et al.

Abstract: Medicinal and aromatic plants, such as wild garlic (Allium ursinum), are valuable sources of bioactive compounds in traditional and modern medicine. However, the challenges in cultivating wild garlic and its seasonality limit its availability primarily to early spring. To maintain the quality of wild garlic, effective postharvest practices are essential, considering the delicate nature of its leaves and their susceptibility to rapid decay. This study focuses on implementing eco-friendly postharvest practices t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…The addition of fresh wild garlic caused a statistically significant increase in the initial concentration of catechin, as well as the detection of a certain concentration of kaempferol derivatives, chlorogenic and ferulic acid. This is in compliance with a report by authors who examined the phenolic profile of wild garlic and proved that kaempferol derivatives were the most dominant [ 28 ]. Carutenuto et al [ 46 ] identified five kaempferol glycosides in the ethanolic extracts of wild garlic, among which two were bound by p -coumaric and ferulic acids.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The addition of fresh wild garlic caused a statistically significant increase in the initial concentration of catechin, as well as the detection of a certain concentration of kaempferol derivatives, chlorogenic and ferulic acid. This is in compliance with a report by authors who examined the phenolic profile of wild garlic and proved that kaempferol derivatives were the most dominant [ 28 ]. Carutenuto et al [ 46 ] identified five kaempferol glycosides in the ethanolic extracts of wild garlic, among which two were bound by p -coumaric and ferulic acids.…”
Section: Resultssupporting
confidence: 92%
“…According to the concentration of detected compounds in cookies with fresh wild garlic leaves (sample 2), kaempferol derivatives were followed by catechin, ferulic, and chlorogenic acids. In the research of Stupar et al [ 28 ], the presence of catechins was confirmed in the extract of wild garlic, obtained by extraction with subcritical water. The presence of ferulic acid is in accordance with the findings of Vlase et al [ 50 ], who detected ferulic and p -coumaric acids in the hydrolyzed and non-hydrolyzed ethanolic extract of wild garlic, while they detected kaempferol only in the hydrolyzed extract.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation